URGENSI KOMUNIKASI PROFETIK PUSTAKAWAN PADA PERPUSTAKAAN UIN SUNAN KALIJAGA YOGYAKARTA - Khotimah, Khusnul (KOMUNIKA, 2019)
This paper discusses the importance of prophetic librarian communication at the SunanKalijaga Yogyakarta UIN Library. Librarians as one of the professions in the midst of society alsoneed the ability to communicate and convey information to the public, especially the librarian. Aspart of UIN Sunan Kalijaga Yogyakarta which is an inclusive tertiary institution, librarians arerequired to communicate with users from different backgrounds. One of the communicationmodels offered in this paper is prophetic communication, which is communication-based onprophetic characteristics. There are three main pillars in this prophetic communication, namelyhumanization, liberation, and transcendence. The implementation of the three pillars discussed inthis paper is the importance of understanding the diversity and style of language used incommunication. Effective communication can create a positive impression which then leads toloyalty in utilizing information sources contained in the library, so the purpose of the library as aninformation and education center and the source of knowledge can be realized.